ANALISIS PORTOFOLIO OPTIMAL MENGGUNAKAN MODEL INDEKS TUNGGAL DAN PENGUKURAN VALUE AT RISK DENGAN SIMULASI MONTE CARLO (Studi Kasus: Exchange Traded Fund di Bursa Efek Indonesia Periode Januari 2021 – Juni 2022) - Vian Rizeki Alif Priyantono; Di Asih I Maruddani; Iut Tri Utami (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2023)
Exchange Traded Fund is one of the investment instruments on the Indonesia Stock Exchange. One way to minimize investment risk is to form an optimal portfolio. This research uses a single index model method in the formation of the optimal portfolio because it has a simpler calculation than other methods, while to measure the Value at Risk (VaR) of the optimal portfolio using Monte Carlo Simulation. The Monte Carlo simulation assumes that the portfolio returns are normally distributed. This research uses ETF data for the period January 2021 to June 2022. The results show that of the seven ETFs sampled, only two ETFs are included in the optimal portfolio, that is XISR (Premiere ETF Sri-Kehati) and XIIT (Premiere ETF IDX-30). Of the two ETFs included in the optimal portfolio, the XISR ETF has a weight of 47.29% while the XIIT ETF has a weight of 52.71% in the formed portfolio, with the VaR estimation in the next month after investing in the optimal portfolio with a 95% confidence level is IDR 58,334,796.00 from the initial capital of IDR 1,000,000,000.00.